2017
DOI: 10.1158/1538-7445.sabcs16-p6-07-06
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P6-07-06: Effect of serum biomarkers (activin A, CAIX, HER2, TIMP-1, and uPA) on outcome in HER2+ metastatic breast cancer patients treated in first line with lapatinib or trastuzumab combined with taxane: CCTG MA.31

Abstract: Background: In MA.31, the lapatinib-taxane combination led to shorter PFS than trastuzumab-taxane in HER2+ metastatic breast cancer. We investigated the prognostic and predictive effects of pretreatment serum biomarkers. Methods: MA.31 accrued 652 patients; 537 (82%) were centrally-confirmed HER2+. Biomarkers were categorized for univariate and multivariate predictive investigations with a median cut-point, ULN cut-points (15 ng/ml- HER2; 506 pg/ml- CAIX; 454 pg/ml- TIMP-1; 1940 pg/ml– uPA; 600 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…24 In summary, until now, there have been no predictive biomarkers identified in the MA.31 trial (ie, none predicting a differential benefit from lapatinib vs trastuzumab). 24 Biomarkers derived from tumor tissue have also been shown to have prognostic benefit in breast cancer. According to results from the FinHER trial of HER2positive early breast cancer, patients with high total tumor HER2 levels (based on VeraTag H2T) derived less benefit from trastuzumab therapy in comparison with those with moderate H2T levels.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…24 In summary, until now, there have been no predictive biomarkers identified in the MA.31 trial (ie, none predicting a differential benefit from lapatinib vs trastuzumab). 24 Biomarkers derived from tumor tissue have also been shown to have prognostic benefit in breast cancer. According to results from the FinHER trial of HER2positive early breast cancer, patients with high total tumor HER2 levels (based on VeraTag H2T) derived less benefit from trastuzumab therapy in comparison with those with moderate H2T levels.…”
Section: Discussionmentioning
confidence: 97%
“…23 Most recently, in this CCTG MA.31 trial, we reported that elevated serum levels of activin A, CA9, HER2, TIMP-1, and uPA were prognostic factors for shorter PFS and OS; however, none were predictive factors for differential outcomes with trastuzumab versus lapatinib. 24 In summary, until now, there have been no predictive biomarkers identified in the MA.31 trial (ie, none predicting a differential benefit from lapatinib vs trastuzumab). 24 Biomarkers derived from tumor tissue have also been shown to have prognostic benefit in breast cancer.…”
Section: Discussionmentioning
confidence: 97%
“…Results from three studies are available as conference abstracts only [45][46][47] . Kang et al evaluated the prognostic and predictive effects of various serum biomarkers, among them uPA, in HER2-positive patients enrolled in the MA.31 trial (NCT00667251) treated by chemotherapy with lapatinib or trastuzumab 45 . Pretreatment serum samples were available for 472 patients; however, it is not clear in how many patients uPA was measured.…”
Section: Discussionmentioning
confidence: 99%